Ceria nanoparticles alleviate myocardial ischemia-reperfusion injury by inhibiting cardiomyocyte apoptosis via alleviating ROS mediated excessive mitochondrial fission - Ying Sun; Jiabao Xu; Ling Zou; Yan Tan; Jie Li; Haoran Xin; Yanli Guo; Weikai Kong; Dingyuan Tian; Xinyu Bao; Xiaoqin Wan; Xiaoxu Li; et al. (Materials Today Bio)
Reperfusion through thrombolytic therapy or primary percutaneous coronary intervention is commonly used to deal with acute myocardial infarction. However, the reperfusion procedure is accompanied by myocardial ischemia-reperfusion injury (MIRI). Currently, there is no therapeutics that can effectively deal with MIRI in clinical practice. Herein, the potential of ceria nanoparticles (CNPs) coated by different ligands in the treatment of rat MIRI is evaluated. The results demonstrate that CNPs can effectively modulate the oxidative stress in the heart tissue through the elimination of reactive oxygen species (ROS) and stimulation of endogenous antioxidant system. The inhibition of oxidative stress results in the reduction of p-Drp1 (Ser 616) which is critical in driving the fission and fragmentation of mitochondria. The improved mitochondrial dynamics saves the cardiomyocytes from apoptosis and reduces the acute injury of left ventricular wall during the MIRI. The ejection function of the left ventricle for both the short-term and long-term MIRI rats is well preserved. We therefore believe based on these results that the administration of CNPs is beneficial in the attenuation of MIRI during the acute stage. These findings provide useful information for the future fabrication of inorganic antioxidant nanomedicine for the treatment of MIRI.